Computer- Assessment of Attention and Memory Utilizing Ecologically Valid Distractions: A Scoping Review - Pinnow, DeAnna; Hubbard, H. Isabel; Meulenbroek, Peter A. (Frontiers in Virtual Reality, 2021)
Introduction: Deficits in the cognitive domains of attention and memory leave a large impact on everyday activities that are not easily captured in the clinical environment. Therefore, clinicians are compelled to utilize assessment tools that elicit everyday functioning that include real-world contexts and distractions. As a result, the use of computer-assisted assessment has emerged as a tool for capturing everyday functioning in a variety of environments. The purpose of this scoping review is to map how virtual reality, augmented reality, and computer-based programs have implemented distractions for clinical populations. Methods: A scoping review of peer-reviewed publications was conducted by searching Pubmed, PsychInfo, Web of Science, Rehabdata, and Scopus databases (1960-October 20, 2020). Authors completed hand-searches for additional published and unpublished studies. Results: Of 616 titles screened, 23 articles met inclusion criteria to include in this review. Primary distraction display modalities included computer monitor displays (n = 13) and head-mounted displays (HMD) (n = 8). While computer-assisted assessments included distractions, no systematic approach was utilized to implement them. Primary distractions included both auditory and visual stimuli that were relevant to the task and/or simulated environment. Additional distraction characteristics emerged including location, timing, and intensity that can contribute to overall noticeability. Conclusion: From this review, the authors reviewed the literature on the implementation of distractions in simulated programming. The authors make recommendations regarding identification, measurement, and programming with suggestions that future studies examining metrics of attention implement distraction in measurable and meaningful ways. Further, the authors propose that distraction does not universally impact performance negatively but can also enhance performance for clinical populations (e.g. instrumental music when completing a focused task).